Every last tie : the story of the Unabomber and his family - Kaczynski, David, 1949- (Duke University Press, 2016)
In August 1995 David Kaczynski's wife Linda asked him a difficult question: "Do you think your brother Ted is the Unabomber?" He couldn't be, David thought. But as the couple pored over the Unabomber's seventy-eight-page manifesto, David couldn't rule out the possibility. It slowly became clear to them that Ted was likely responsible for mailing the seventeen bombs that killed three people and injured many more. Wanting to prevent further violence, David made the agonizing decision to turn his brother in to the FBI. Every Last Tie is David's highly personal and powerful memoir of his family, as well as a meditation on the possibilities for reconciliation and maintaining family bonds